HYPERMEDIA DEVELOPMENT AS SELF-REGULATED LEARNING RESOURCES FOR HIGH SCHOOL ENGLISH DEBATING TRAINING - Ubaidah Ubaidah (Business Economic, Communication, and Social Sciences (BECOSS) Journal, 2019)
This research was aimed to develop Hypermedia as an alternative learning resources that support self-regulated learning implementation for English Debating Training in Highschool. The product was developed by the framework of web-based learning environment development model. To ensure the eﬀectivity of the product, hypermedia was tested on formative and sumative evaluation involving expert, teacher, and students as participants. At the end of the study, the product was found eﬀective which is indicated by (1) 80% of students often use this hypermedia at their home as self-regulated learning resources, (2) the improvement of students debating knowledge which indicated by the improvement test result by 3.3 poin, and (3) outstanding the students’ achievement of debating competencies that 50% of the students have above average debating skills after learning with hypermedia “Enjoy Your Debate!”